Numerical simulations of liquefaction resistance of seabed under wave conditions. Issue 3 (3rd July 2018) - Zhang, Jin-feng; Deng, Bin; Chen, Tong-Qing; Yan, Bing; Chen, Bao-Qing
ABSTRACT: Limited research exists on numerical simulation of liquefaction-resistant measures. In this study, a coupling model that combined computational fluid dynamics method with computational structure dynamic within the OpenFOAM framework is adopted to study the dynamic response of the seabed under cyclic wave action. The pore pressure and effective stresses of cover stones on a liquefiable bed under wave conditions are investigated. It can be concluded that the number of stone layers and the porosity of the cover stones are two important parameters for the seabed dynamic response under wave conditions. Additionally, the liquefaction-resistant measure with stones primarily alters the effective stresses of the soil; thus, the liquefaction-resistant capacity of the soil is enhanced.